Mengevaluasi Efektivitas Promosi UKM Al Huda Menggunakan Social Media Analytic - Niazi, Hakam Ali; Oktaviani, Retno Fuji; Dewi, Yesi Puspita (Penerbit Goodwood, 2025)
Purpose: This research aims to evaluate how well social media platforms and their analytics tools contribute to the success of marketing efforts in expanding the reach and sales of UKM Al Huda. Methodology/approach: The study was conducted at the location of UKM Al Huda, utilizing social media analytics tools such as Google Analytics, and Instagram Insights. Data collection methods included online surveys and reviews of social media performance, which helped in analyzing the effectiveness of the promotional strategies based on the collected data. Results/findings: The findings of this study indicate that social media analysis significantly increases the visibility of Al Huda SME products. This in turn leads to increased customer engagement and improved sales performance, highlighting the positive impact of social media marketing on business. Based on the pre-test results, an 80% increase in participants' abilities was obtained from the participants' abilities before participating in the Social Media Analysis training. Conclusion: Pelatihan UKM Al Huda berhasil meningkatkan pemahaman strategi pemasaran digital, pemanfaatan media sosial, dan analitik. Evaluasi menunjukkan peningkatan keterampilan anggota dalam memasarkan produk secara online. Keberlanjutan program diharapkan mendorong perluasan pasar dan peningkatan penjualan. Limitations: The study is limited by a relatively short observation period and the reliance on available social media data, which may not fully represent the entirety of UKM Al Huda's marketing efforts. Contribution: This study contributes to the field of digital marketing by providing valuable insights into the impact of social media analytics on small and medium-sized enterprises (SMEs).